Dialetics and Poetry. Reading Haroldo de Campos - Santos, Acácio Luiz (Revista de Letras, 2007)
This essay aims to discuss dialectical transformations in Haroldo de Campos' poems from 1949 to 1962, which can be divided into three periods: from Auto do possesso to early Noigandres poems, from early Noigandres poems to concrete poems, and from concrete poems to "Servidão de passagem". In the first period, the dialectical transformation starts from myth and paideia and changes into oppositional attitudes. In the second, the quest for "essential silence" and values of "vital language" is transformed in extreme experiences with form and visual aspects. Finally, critical view of reality turns into social and ideological protests. Thus, all these dialectical transformations emerge from a tension between identity and difference, and the essay intents to contribute for a most comprehensive knowledge of Campos' poetic output.